SYNTHESIS, CHARACTERIZATION AND DEACTIVATION STUDIES OF PROMOTED NICKEL-BASED CATALYSTS FOR CARBON DIOXIDE REFORMING OF METHANE - YAHYA, ERNY AZWIN (2018)
CO2 reforming of methane (CDRM) can be an attractive option to utilize two main greenhouse gases for syngas production. However, the main drawback of this reaction is the rapid deactivation of the catalyst. This work focused on synthesis of 9 wt% Nibased catalysts via wet impregnation method, evaluation of their catalytic activity and deactivation behavior in CDRM reaction.